Exchange rate and the demand for money in Malaysia - Mohamed, Azali; Baharumshah, Ahmad Zubaidi; Habibullah, Muzafar Shah (Universiti Putra Malaysia Press, 2000)
This paper investigates the long run relationship between exchange rate and money demand in Malaysia. The Johansen:Juselius (1990) likelihood ratio tests support the importance of exchange rate in m2 but not in ml money demand. The Hansen:Johansen (1993) likelihood ratio tests however found some evidence of instability in the long run parameters and this could be due to the recent financial crisis in this region. Overall analysis has provided support to the empirical investigation of the relation between exchange rate and money demand.